Penyusunan Laporan Keuangan Berdasarkan SAK EMKM dan Pengukuran Kinerja Keuangan Pada Perusahaan Jual Beli Barang Bekas (Studi Kasus Pada PD. XYZ) - Linda Luciana; Arwan Gunawan (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
Financial reports are one of the important sources of information for MSMEs in the financial decision-making process and the components which can be used to measure financial performance. However, not all UMKM compile financial reports, one of them is PD. XYZ. In the absence of financial reports, PD. XYZ has difficulty in making financial decisions. The aim of this research is to help PD. XYZ prepares financial reports and to find out its financial performance. This type of research is a mixed method. The results showed that the financial records of PD. XYZ is still simple, which only records petty cash receipts and petty cash disbursements. Then, PD. XYZ has not prepared a financial report due to the lack of understanding of the owner and his financial department regarding accounting. In addition, based on the measurement of financial performance, the results show that the solvency ratio and the company's activity ratio in the March and April 2020 periods were efficient, while the liquidity ratios and profitability ratios were inefficient.